Group B Streptococcus infection: epidemiology, serotypes, and antimicrobial susceptibility of selected isolates in the population beyond infancy (excluding females with genital tract- and pregnancy-related isolates) at the University Malaya Medical Centre, Kuala Lumpur. - Karunakaran, R.; Raja, N.S.; Hafeez, A.; Puthucheary, S.D. (Institute of Infectious Diseases, 2009)
Group B Streptococcus (GBS) infection was studied in 49 patients collected at convenience (convenience sampling), excluding infants and women with genital tract- and pregnancy-related isolates, according to the availability of stocked isolates and easy accessibility to epidemiological data. The data were examined both prospectively and retrospectively from 2003-2005 at a tertiary-level multidisciplinary hospital in Kuala Lumpur, Malaysia. Skin and soft-tissue infections in 35 patients (71.4%) were the most common clinical presentation, while diabetes mellitus was the most common underlying condition (35 patients, 71.4%). All GBS isolates were sensitive to penicillin, and most isolates tested were sensitive to erythromycin (97.7%). Serotyping of 45 GBS isolates using a commercial serotyping kit revealed that the most common serotype was Ia (22.2%), followed by VI (17.8%), III and V (13.3% each). Others included Ib, II, IV, VIII, and VII; 13.3% were nontypeable. The findings of this pilot study are limited by the small sample size, the sampling method and the possibility that the cases are not wholly representative of the University Malaya Medical Centre population. Further studies from our hospital with larger numbers and using probabilistic sampling techniques are required to confirm the relatively high occurrence of serotype VI (the second most common serotype) in the population studied.